Selective gene expression profiling of mTOR-associated tumor suppressor and oncogenes in ovarian cancer - Lech Chyczewski; Jacek Szamatowicz; Radosław Charkiewicz; Włodzimierz Baranowski; Magdalena Garbowicz; Dominik Rysak-Luberowicz; Tomasz Milczek; Dagmara Klasa-Mazurkiewicz; Oksana Kowalczuk; Piotr Laudański (Folia Histochemica et Cytobiologica, 2011)
The aim of this study was to selectively profile the activation status of mammalian target of rapamycin (mTOR)-associated oncogenes and tumor suppressor genes (TSGs) in ovarian cancer specimens, healthy ovaries and benign ovarian tumors, including endometrial cysts. We used a novel type of microfluidic gene array to examine the expression of 15 human tumor suppressors and oncogenes in ovarian cancer specimens of 53 patients, benign ovarian cysts of 29 women (endometrial and simple) and 11 healthy ovaries of individuals in whom the material was obtained during total hysterectomies performed because of fibroid changes. The array was custom-designed to include the following genes: NF1, RHEB, mTOR1, AKT-1, PTEN, TSC1, TSC2, KRAS, RPS6KB1, 4EBP1, TP53, EIF4E, STK11, PIK3CA and BECN1. Confirmatory immunohistochemical detection was performed for a group of selected proteins. Particularly significant differences were observed as to the expression of PTEN (p < 0.0001), TP53 (p = 0.0003), PIK3CA (p = 0.0003) and BECN1 (p = 0.0014) which were shown to be downregulated in cancer patients when compared to healthy ovaries and benign ovarian cysts (endometrial and simple). These markers did not show association with grade or stage of the tumor. Immunohistochemistry showed that PTEN, TP53, PIK3CA and BECN1 proteins are expressed in ovarian cancer. Our results indicate that there are significant differences in the expression of some of the mTOR-related tumor suppressors and oncogenes which could be associated with the pathogenesis of ovarian cancer. (Folia Histochemica et Cytobiologica 2011; Vol. 49, No. 2, pp. 317–324)